Contextualised peak periods of play in English Premier League matches - Ju, W.; Doran, D.; Hawkins, R.; Gómez-Díaz, A.; Martin-Garcia, A.; Ade, J.; Laws, A.; Evans, M.; Bradley, P. (Biology of Sport, 2022)
The present study aimed to determine the physical-tactical trends of elite players/teams during peak 1-, 3- and 5-min periods of match-play. A total of 50 English Premier League matches (n = 583 player observations) were analysed by coding the players` physical-tactical activities through the synchronisation of tracking data and video. The contextualised data showed that during the peak periods (i.e., the most demanding passage of play), players/teams covered the largest distances for `Recovery Run` (28-37%) out of possession and `Support Play` (9-13%) in possession. In the following periods, players covered less high-intensity distance versus the average with a more pronounced decline in the next 1-min period than longer duration 3- and 5-min periods (48% vs ~25-30%, ES: 0.4-0.5, P < 0.01); team data showed similar trends with different relative patterns (31% vs 17-30%, ES: 0.5-0.8, P < 0.01). After peak periods, players/teams performed 20-53% less high-intensity distances for `Covering` and `Recovery Run` (ES: 0.2-0.7, P < 0.01) out of possession. However, players covered 28-91% less distance for `Run with Ball` (ES: 0.1-0.5, P < 0.05) when in possession. Some physical-tactical actions exhibited inconsistency in different time durations of the next periods; however, these physical-tactical data were position-specific. This may signify that each position has certain physical-tactical actions to execute even after the peak periods, especially when they are tactically required to do so. As the data demonstrates unique physical-tactical trends of players/teams during the peak and next periods of play, this could help practitioners prescribe position- and player-specific drills, and better understand transient decrements in high-intensity running after intense passages of play.